Local theorems of large deviations for homogeneous Markov chains - Misevičius, E. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. В. Мисевичюс. Локальные теоремы с большими уклонениями для однородных цепей Маркова E. Misevičius. Didelių nukrypimų lokalinės teoremos homogeninėms Markovo grandinėms